(untitled) (Global Journal of Management and Business Research, 2012)
The aim of this article is to get the A study to point towards role of packaging on consumer buying behavior. The basic purpose of this it is to find out how such factors are behind the success of packaging. The purpose of this research is to know the relationship between independent variable and dependent variables. The research is based in Patan District of Gujarat (India). The packaging is the most important factor. The consumer buying behavior is dependent on the packaging and on its features. Packaging elements like Packaging color. Background Image, Packaging Material, Font Style, Design of wrapper, Printed Information and Innovation is taken as predictors. Due to increasing self-service and changing consumers#x2019; lifestyle the interest in package as a tool of sales promotion and stimulator of impulsive buying behavior is growing increasingly. So package performs an important role in marketing communications, especially in the point of sale and could be treated as one of the most important factors influencing consumer#x2019;s purchase decision.